Graphene composite film and preparation method and application thereof

By introducing a three-dimensional carbon skeleton into the graphene film and compounding it with graphene to form a three-dimensional network structure, the problem of insufficient longitudinal thermal conductivity of the graphene film is solved, and a composite film with high thermal conductivity and high strength is achieved, which is suitable for thermal management materials.

CN120757106APending Publication Date: 2025-10-10BEIJING GRAPHENE INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410361872.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-27
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

The longitudinal thermal conductivity of existing graphene films is low, making it difficult to meet the needs of efficient heat dissipation.

Method used

采用三维碳骨架与石墨烯复合,通过在真空环境下浸渍氧化石墨烯浆料并进行高温碳化、石墨化处理,形成石墨烯填充的三维网络结构,结合压延处理以提高纵向导热性。

Benefits of technology

The longitudinal thermal conductivity of the graphene composite film was increased to ≥6W/(m·K), while maintaining the transverse thermal conductivity ≥1500W/(m·K) and the strength ≥14GPa, expanding its application in the field of thermal management.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120757106A_ABST
    Figure CN120757106A_ABST
Patent Text Reader

Abstract

The invention provides a graphene composite film and a preparation method and application thereof. The graphene composite film comprises a three-dimensional carbon skeleton and graphene coated on the surface of the three-dimensional carbon skeleton and / or filled in the three-dimensional carbon skeleton, the thickness of the graphene composite film is 1-2mm, the transverse thermal conductivity is greater than or equal to 1500W / (m.K), the longitudinal thermal conductivity is greater than or equal to 6W / (m.K), and the strength is greater than or equal to 14GPa. According to the graphene composite film, the three-dimensional carbon skeleton serves as a supporting structure, the graphene sheet covers the surface of the three-dimensional carbon skeleton and / or fills the three-dimensional carbon skeleton, the three-dimensional skeleton and the graphene sheet form a three-dimensional network structure, transverse heat conduction of a traditional graphene film is kept, meanwhile, longitudinal heat conduction is enhanced, and three-dimensional high heat conduction is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of thermal management materials, and particularly relates to a composite film and a preparation method and application thereof. BACKGROUND

[0002] Thermal management materials are widely used to keep large power electronic devices cool and ensure that the devices operate at high speed, high efficiency and long-term reliability. However, efficient heat dissipation related to the development of large power and high integration devices has always been a technical engineering problem. In the past few years, metal materials have been widely used in thermal management components of electronic devices due to their acceptable isotropic thermal conductivity. Subsequently, graphene thermal conductive films have become a hot material for thermal management due to their excellent thermal conductivity. As a member of thermal management materials, the requirements for graphene thermal conductive films are becoming higher and higher with the continuous updating of electronic devices.

[0003] As an interface heat dissipation material, the longitudinal heat dissipation performance of the graphene film is also important. The existing axial (longitudinal) thermal conductivity coefficient of the graphene film is generally below 5 W / (m·K), and the research on improving the axial (longitudinal) thermal conductivity performance of the graphene film is relatively less.

[0004] In order to expand the application of graphene thin films in the field of thermal management, it is urgent to solve the problem of low longitudinal thermal conductivity coefficient of conventional graphene thermal conductive films. SUMMARY

[0005] In order to solve the above problems, the present application provides a composite film and a preparation method thereof.

[0006] The present application provides a graphene composite film, which comprises a three-dimensional carbon skeleton and graphene coated on the surface of the three-dimensional carbon skeleton and / or filled in the three-dimensional carbon skeleton, the lateral thermal conductivity of the graphene composite film is greater than or equal to 1500 W / (m·K), the longitudinal thermal conductivity is greater than or equal to 6 W / (m·K), and the strength is greater than or equal to 14 GPa.

[0007] According to an embodiment of the present application, the mass content of graphene in the graphene composite film is 70%-80%.

[0008] According to another embodiment of the present application, the thickness of the graphene composite film is 1mm-2mm, and the density is 1.8-2.1g / cm 3 .

[0009] The second aspect of the present application provides a preparation method of a graphene composite film, comprising: providing graphene oxide slurry; immersing a three-dimensional porous material in the graphene oxide slurry under a vacuum environment, so that the graphene oxide fills into pores of the three-dimensional porous material to obtain graphene oxide filled three-dimensional material; and sequentially performing high-temperature carbonization and graphitization on the graphene oxide filled three-dimensional material to obtain graphene filled three-dimensional material; and performing calendering treatment on the graphene filled three-dimensional material to form the graphene composite film.

[0010] According to an embodiment of the present application, the three-dimensional porous material is felt formed by one or more of polyacrylonitrile fiber, pitch-based fiber, aramid fiber, spandex fiber, carbon fiber, nylon 6 fiber, nylon 11 fiber, and nylon 66 fiber, the thickness of the three-dimensional porous material is 1.2 mm-3 mm, and the porosity is 60%-70%; preferably, the three-dimensional porous material is polyacrylonitrile felt or pitch-based felt.

[0011] According to another embodiment of the present application, the preparation method of the graphene oxide slurry comprises: dispersing graphene oxide in deionized water to obtain graphene oxide dispersion liquid with a mass fraction of 3%-5%, adjusting the pH of the graphene dispersion liquid to 6-8, and then performing homogenization and defoaming treatment on the dispersion liquid to obtain the graphene oxide slurry with a viscosity of 10000-25000 mPa·s, and the particle size of the graphene oxide slurry is controlled to be 0.2-40 μm.

[0012] According to another embodiment of the present application, the carbonization process adopts gradient heating to 1000-1200℃, the heating process lasts for 8-10 h, and then the holding time is 0.5-1 h, and the pressure of the carbonization process is kept in a negative pressure state less than atmospheric pressure; the graphitization process is performed under inert gas protection, the processing temperature is 2800-3100℃, the heating time is 6-12 h, and the holding time is 0.5-2 h.

[0013] According to another embodiment of the present application, the pressure of the calendering treatment is 20-100 MPa, and the pressing time is 2-10 h.

[0014] The third aspect of the present application provides a graphene composite film prepared by the above method.

[0015] The fourth aspect of the present application provides application of the above graphene composite film in the field of thermal management.

[0016] The graphene composite film of the present application takes a three-dimensional carbon skeleton as a support structure, graphene sheets cover the surface of the three-dimensional carbon skeleton and / or fill in the three-dimensional carbon skeleton, the three-dimensional carbon skeleton and the graphene sheets form a three-dimensional network structure, the graphene composite film maintains the transverse thermal conductivity of traditional graphene films, and the longitudinal thermal conductivity is enhanced, thereby realizing three-dimensional high thermal conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a photo of the composite film prepared in Example 1.

[0018] Figure 2A 、 Figure 2B and Figure 2C These are microstructure diagrams of the composite film prepared in Example 1 at different positions and different magnifications. DETAILED DESCRIPTION

[0019] The present invention will be described in detail below with reference to specific embodiments.

[0020] The graphene composite film of the present invention comprises a three-dimensional carbon skeleton and graphene coated on and / or filled within the three-dimensional carbon skeleton. The graphene composite film has a transverse thermal conductivity of ≥1500 W / (m·K), a longitudinal thermal conductivity of ≥6 W / (m·K), and a strength of ≥14 GPa. In the graphene composite film of the present invention, the three-dimensional carbon skeleton and the graphene sheets form a three-dimensional network structure. The three-dimensional carbon skeleton provides longitudinal thermal conductivity, thereby maintaining the lateral thermal conductivity of traditional graphene films while enhancing longitudinal thermal conductivity, achieving high three-dimensional thermal conductivity.

[0021] The mass content of graphene in the graphene composite film is 70%-80%. The thickness of the graphene composite film is 1mm-2mm and the density is 1.8-2.1g / cm 3 .

[0022] The method for preparing a graphene composite film of the present invention comprises providing a graphene oxide slurry; impregnating a three-dimensional porous material into the graphene oxide slurry under a vacuum environment, so that the graphene oxide is filled into the pores of the three-dimensional porous material to obtain a graphene oxide-filled three-dimensional material; sequentially performing high-temperature carbonization and graphitization on the graphene oxide-filled three-dimensional material to obtain a graphene-filled three-dimensional material; and calendering the graphene-filled three-dimensional material to form a graphene composite film.

[0023] First, the three-dimensional porous material is immersed in a graphene oxide slurry and placed in a closed environment for vacuum treatment, so that the air in the three-dimensional porous material is squeezed out, and the graphene oxide enriched on the surface of the three-dimensional porous material enters and stays in the pores of the three-dimensional porous material. After carbonization and graphitization treatment, the three-dimensional porous material serves as a three-dimensional carbon skeleton of the composite film, and the graphene oxide and the three-dimensional carbon skeleton form a three-dimensional grid structure. The three-dimensional carbon skeleton provides longitudinal thermal conductivity, thereby improving the longitudinal thermal conductivity of the graphene material while maintaining the lateral thermal conductivity of the graphene. This step fills the graphene oxide into the three-dimensional porous material in a vacuum environment, which can improve the filling amount and uniformity of the graphene oxide, thereby obtaining a composite film with more uniform thermal conductivity. The preparation method of the graphene oxide slurry can be to disperse graphene oxide in deionized water to obtain a graphene oxide dispersion liquid with a mass fraction of 3% to 5%. The dispersion process can be stirred at a speed of 1800 to 2500 r / min to improve the dispersibility of the graphene oxide, and the dispersion time can be determined according to specific conditions, for example, 1 to 5 hours. Then, the pH value of the dispersion liquid is adjusted to 6 to 8. Preferably, ammonia is used to adjust the pH of the dispersion liquid to avoid introducing impurities that affect the thermal conductivity. Then, the dispersion liquid is subjected to homogenization and defoaming treatment. The homogenization pressure is 60 to 100 MPa, and the graphene oxide slurry with a viscosity of 10000 to 25000 mPa·s is obtained. The slurry particle size is controlled between 0.2 to 40 μm. A viscosity of 10000 to 25000 mPa·s can enable the graphene oxide dispersion liquid to be fully filled into the pores and meet the filling amount requirements. Controlling the slurry particle size between 0.2 to 40 μm is beneficial to the rearrangement of carbon atoms during the graphitization process, thereby improving the thermal conductivity. After the above immersion, the graphene oxide is loaded into the three-dimensional porous material to obtain a graphene oxide-filled three-dimensional material.

[0024] Afterwards, the graphene oxide filled three-dimensional material is subjected to high-temperature carbonization and graphitization treatment. The carbonization process reduces the graphene oxide to defective graphene, and the defective graphene is rearranged to form high-heat-conducting graphene in the graphitization process, while the three-dimensional porous material is converted into carbon felt through the carbonization and graphitization processes. The three-dimensional porous material used in the present application can be, for example but not limited to, one or several of polyacrylonitrile fibers, pitch-based fibers, aramid fibers, spandex fibers, carbon fibers, nylon 6 fibers, nylon 11 fibers, and nylon 66 fibers. Preferably, it is polyacrylonitrile (PAN) felt or pitch-based felt, which will undergo graphitization in the graphitization treatment step of the graphene oxide, obtaining carbon felt with excellent heat conduction performance; compared with directly using carbon felt, the structural strength of the material can be effectively guaranteed. The graphene oxide filled three-dimensional material can be dried before the carbonization treatment, or the drying step can be completed simultaneously during the carbonization treatment. When the graphene oxide filled three-dimensional material is subjected to drying treatment, the temperature of the drying treatment can be 40-50℃, and the drying time can be 6-8h. The temperature of the carbonization process can be 1000-1200℃. The carbonization process can adopt a gradient heating process, the heating process is 8-10h, and the holding time is 0.5-1h. The carbonization can be carried out under negative pressure. The temperature of the graphitization treatment can be 2800-3100℃, the heating time can be 6-12h, the holding time is 0.5-2h, and the atmosphere is an inert gas to the reaction, for example but not limited to nitrogen. After the high-temperature carbonization and graphitization steps, the graphene filled three-dimensional material is obtained.

[0025] Finally, the graphene filled three-dimensional material is subjected to calendering treatment. Through the calendering treatment, the air in the film can be further discharged, and reducing the air content in the film can effectively reduce the interfacial thermal resistance and improve the heat conductivity of the material. The pressure of the calendering treatment can be 20-100MPa, and the pressing time can be 2-10h.

[0026] The composite film prepared by the above method has a transverse thermal conductivity of ≥1500W / (m·K), a longitudinal thermal conductivity of ≥6W / (m·K), and a strength of ≥14GPa. The mass content of graphene in the graphene composite film is 70%-80%. The thickness of the graphene composite film is 1mm-2mm, and the density is 1.8-2.1g / cm 3 .

[0027] The composite film of the present application increases the longitudinal thermal conductivity while maintaining the transverse thermal conductivity, which can expand the application of the composite film in the field of thermal management.

[0028] The present application will be further described by specific examples. However, these examples are merely exemplary and do not constitute any limitation on the scope of protection of the present application. In the following examples and comparative examples, the reagents, materials and instruments used are commercially available unless otherwise specified.

[0029] Example 1

[0030] The graphene oxide dispersion was prepared by dispersing graphene oxide in deionized water at a rotation speed of 2000 r / min for 1 h to obtain a graphene oxide dispersion with a mass fraction of 4%. Ammonia was used to adjust the pH of the graphene oxide dispersion to 7. The dispersion was then subjected to homogenization and defoaming treatment, and the pressure during homogenization was 80 MPa to obtain a graphene oxide slurry with a viscosity of 25000 mPa·s. The median particle size of the slurry was 40 μm.

[0031] The PAN felt (thickness of 3 mm, porosity of 65%) was immersed in the slurry prepared above and placed in a sealed environment for vacuum treatment and left in the vacuum environment for 12 h.

[0032] The film obtained in the previous step was dried in an oven at a temperature of 50°C for 8 h.

[0033] The film obtained in the previous step was carbonized in a carbonization furnace at a temperature of 1200°C. The carbonization process was performed in a gradient heating process, and the heating process lasted for 10 h, and the holding time was 1 h. The carbonization was performed under negative pressure.

[0034] The film obtained in the previous step was graphitized in a graphitization furnace at a temperature of 3100°C. The heating time was 12 h, and the holding time was 2 h. The atmosphere was treated with nitrogen.

[0035] The film obtained in the previous step was subjected to calendering treatment, and the equipment pressure was 100 MPa, and the pressing time was 2 h.

[0036] The obtained graphene thermal conductive composite film had a thickness of 1.2 mm and a density of 2.0 g / cm 3 The prepared composite film was tested for thermal conductivity and strength. The test methods are as follows:

[0037] Thermal conductivity test: laser flash method was used, and the instrument used was Netzsch LFA467, and the test standard was ASTM-E1461.

[0038] Strength test: the tensile strength of the composite film was tested by using a tensile testing machine / universal testing machine, and the standard was GB / T 1040.

[0039] After the above tests, the transverse thermal conductivity of the composite film prepared in Example 1 was 1500 W / (m·K), the longitudinal thermal conductivity was 13 W / (m·K), and the strength was 20 GPa.

[0040] Example 2

[0041] The three-dimensional porous material was carbon felt, and the other conditions were the same as in Example 1.

[0042] The obtained graphene heat-conducting film has a thickness of 1 mm, a density of 2.0 g / cm 3 , a transverse heat conductivity of 1500 W / (m·K), a longitudinal heat conductivity of 6 W / (m·K), and a strength of 14 GPa.

[0043] Comparative Example 1

[0044] The impregnation step is performed at normal pressure, and other conditions are the same as in Example 1.

[0045] The obtained graphene heat-conducting film has a thickness of 1.8 mm, a density of 1.65 g / cm 3 , a transverse heat conductivity of 1250 W / (m·K), a longitudinal heat conductivity of 5 W / (m·K), and a strength of 6.4 GPa.

[0046] Comparative Example 2

[0047] No final calendering treatment is performed, and other conditions are the same as in Example 1. The obtained graphene heat-conducting film has a thickness of 2.0 mm, a density of 1.2 g / cm 3 , a transverse heat conductivity of 800 W / (m·K), a longitudinal heat conductivity of 4 W / (m·K), and a strength of 26 GPa.

[0048] Figure 1 、 Figure 2A 、 Figure 2B and Figure 2C are photographs of the composite film prepared in the examples and magnified images of different positions. As can be seen from the figures, the graphene film and the three-dimensional material form a grid structure in the composite film of the application, achieving three-dimensional heat conduction of the composite film.

[0049] As can be seen from Comparative Example 1 and Comparative Example 1, the impregnation in the application is performed in a vacuum environment, which can improve the filling rate of graphene oxide and thus improve the heat conductivity of the graphene composite film. As can be seen from Comparative Example 1 and Comparative Example 2, the graphene-filled three-dimensional material is subjected to a final calendering treatment in the application, which reduces the air content in the film and effectively reduces the interfacial thermal resistance, thereby improving the heat conductivity of the composite film.

[0050] As can be seen from Comparative Example 1 and Example 2, the use of carbon felt improves the longitudinal heat conductivity compared to Comparative Examples 1 and 2, but the structural strength of the composite film is reduced compared to the use of PAN felt.

[0051] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A graphene composite film, characterized in that The graphene composite film comprises a three-dimensional carbon skeleton and graphene coated on the surface of the three-dimensional carbon skeleton and / or filled in the three-dimensional carbon skeleton. The graphene composite film has a transverse thermal conductivity of ≥1500 W / (m·K), a longitudinal thermal conductivity of ≥6 W / (m·K), and a strength of ≥14 GPa.

2. The graphene composite film according to claim 1, wherein The mass content of graphene in the graphene composite film is 70%-80%.

3. The graphene composite film according to claim 1, wherein The graphene composite film has a thickness of 1 mm to 2 mm and a density of 1.8 to 2.1 g / cm 3 .

4. A method for preparing a graphene composite film, characterized in that: include: Providing graphene oxide slurry; impregnating a three-dimensional porous material into the graphene oxide slurry under a vacuum environment, so that the graphene oxide fills the pores of the three-dimensional porous material to obtain a graphene oxide-filled three-dimensional material; The graphene oxide-filled three-dimensional material is sequentially subjected to high-temperature carbonization and graphitization to obtain a graphene-filled three-dimensional material; The graphene-filled three-dimensional material is subjected to a calendering process to form the graphene composite film.

5. The method for preparing a graphene composite film according to claim 4, wherein: The three-dimensional porous material is a felt formed by one or more of polyacrylonitrile fiber, asphalt-based fiber, aramid fiber, spandex fiber, carbon fiber, nylon 6 fiber, nylon 11 fiber, and nylon 66 fiber. The thickness of the three-dimensional porous material is 1.2 mm to 3 mm, and the porosity is 60% to 70%. Preferably, the three-dimensional porous material is polyacrylonitrile felt or asphalt-based felt.

6. The method for preparing a graphene composite film according to claim 4 or 5, wherein: The preparation method of the graphene oxide slurry includes: dispersing graphene oxide in deionized water to prepare a graphene oxide dispersion with a mass fraction of 3% to 5%, adjusting the pH of the graphene dispersion to 6 to 8; then homogenizing and defoaming the dispersion to obtain the graphene oxide slurry with a viscosity of 10,000 to 25,000 mPa·s, and controlling the particle size of the graphene oxide slurry to be between 0.2 and 40 μm.

7. The method for preparing a graphene composite film according to claim 4 or 5, wherein: The carbonization process adopts a gradient temperature increase to 1000-1200°C, the temperature increase process is 8-10 hours, and then the temperature is kept at a temperature of 0.5-1 hour. The pressure of the carbonization process is maintained at a negative pressure state less than atmospheric pressure; The graphitization process is carried out under the protection of inert gas, the treatment temperature is 2800-3100° C., the heating time is 6-12 hours, and the heat preservation time is 0.5-2 hours.

8. The method for preparing a graphene composite film according to claim 4 or 5, wherein: The pressure of the calendering treatment is 20-100 MPa, and the pressing time is 2-10 hours.

9. A graphene composite film, characterized in that Prepared by the preparation method according to any one of claims 4 to 8.

10. Use of the graphene composite film according to any one of claims 1 to 3 and 9 in the field of thermal management.